Moderasi Pengawasan Perpajakan atas Pengaruh Penggunaan E-Form dan Edukasi Perpajakan Terhadap Kepatuhan Wajib Pajak Pebisnis E-Commerce - Rio Johan Putra; Mei Welensya Br Simatupang (Universitas 17 Agustus 1945 Jakarta, 2022)
This article proves the effect of the Use of E-Form and Tax Education on Taxpayer Compliance of E-commerce Businessmen moderated by Tax Supervision. The results tested, the effect of using e-forms and Tax Education on Taxpayer Compliance of E-commerce Businessmen. The sample of this research is 220 respondents from the E-commerce Businessmen. The analysis uses Structural Equation Modeling to test this research model. Next, examine the effect of the Effect of E-Form Use and Tax Education on Taxpayer Compliance of E-commerce Businesses moderated by Tax Supervision. The results of the study prove that Tax Education has proven to have an impact on E-commerce Business Taxpayer Compliance. Then, Moderation of Tax Supervision on Taxation Education proved to have an effect on E-commerce Business Taxpayer Compliance. The results of this study recommend that creating E-commerce Businessman Taxpayer Compliance in individuals is to have adequate Tax Education within the Taxpayer.